(untitled) (Journal Of Educational and Psychological Researches, 2011)
A school uniform is an international educational phenomenon , and that each state through its pedagogical educational system imposes uniform hopping for goals and visions that complement their theoretical framework, because of its extreme importance that benefits the school administration, parents and pupils . The carried out researches unanimous in various parts of the world on its importance, including : the achievement of equality between students and strengthen their affiliation to the school as well as the good appearance , and reduces competition in the clothing and the maintenance of order in the classroom and school as well as increases the seriousness and focus of students to study and make them known both inside and outside the school and regulate their attendance for school without hesitation. . It was therefore necessary to focus on school uniform ( its designs , fabrics and colours ) so as to clothes in general and school uniforms special , privacy when girls in the stage of late childhood, "because they are more interested in fashion" as well as their tendency to favor the others desirability and specially their peers, and their quest to confirm their esteem by their interest for clothing and express their opinion as naturally inclined and their ability to debate and dialogue about what preferably, their preferences affected by conditions, traditions of society, the environment which they live in and the nature of their activities . The preferences of elementary school girls of samples of school uniforms may help designers and officials in the ready-made clothes factories to manufacture comfortable school uniforms to make them feel happy and have a right to express their opinion and makes it easier for parents to provide uniform . For all of that, the current research goal to identify the ( The designs and fabrics of school uniform preferred by the elementary stage girls ). A sample of research which covers ( 1260 ) females aged ( 9-12 ) years were chosen from the ranks of the fourth, fifth and sixth year from (14) elementary school located in the center of the province of Baghdad , (8) schools in the Rusafa and (6) schools in the Karkh district . The researcher was carried out the samples by herself accurately according to the correct sewing foundations which include ( the preparation of the pattern , cutting , marking , sewing, termination and ironing) in (5) samples dressed on five similar dolls that can be carried . The most important findings of the research: - - The model number ( 2 ) (a shirt coloured in light heavenly and jumper coloured in low dark blue ) as the first choice , followed by the model number (4) ( a shirt coloured in yellow and jumper oily colour ) , then the model number ( 3 ) (a shirt coloured in light beige and jumper coloured in brown ) , followed by the model number ( 5 ) ( a shirt in light pink and jumper coloured in dark violet ) , and finally the model number ( 1) (a shirt coloured in gray and jumper coluored in maronite ) . Finally, the researcher suggested some of her recommendations and proposals .